Implikatur Percakapan Di Balik Tuturan Pejabat Pemerintah Pada Surat Kabar Harian Jawa Pos Radar Solo dan Implementasinya Sebagai Bahan Ajar Bahasa Indonesia di SMK - Setiyaningsih, Wahyu, Prof. Dr. Harun Joko Prayitno, M.Hum, Prof. Dr. Abdul Ngalim, M.Hum (2016)
The purpose of this study is to describe the shape and function of conversational implicature behind the utterances of government officials, as well as the implementation of learning Indonesian teaching materials at Muhammadiyah University of Surakarta. Research was conducted on the speech of government officials in a daily newspaper Jawa Pos Radar Solo, by using qualitative descriptive methods, and uses fixed strategy (embedded research). Data collection techniques in this study using the technique see and record. There are three things as a result of research on the form and function of conversational implicature behind utterances government officials consisting of 26 data. 1) the form of conversational implicature behind the utterances of government officials at the daily newspaper Jawa Pos Radar Solo contains two types namely, conversational implicatures conventional states assertive as much as 2 data or 8%, and nonconventional stating directive as much as 9 data, or 34%, as well as states commissive much as 2 data or 8%. 2) the function of conversational implicature behind the utterances of government officials at the daily newspaper Jawa Pos Radar Solo expressing the message as much as 2 data or 8%, said command as much as 9 data, or 34%, and a promise by 2 data or 8% 3) These findings can be implemented as Indonesian teaching materials pragmatic course 4 th semester at the University of Muhammadiyah Surakarta.